Características físico-químicas de amidos de genótipos de bananeiras - Mesquita, Camila de Barros [UNESP] (2015)
Banana (Musa spp.) is one of the most cultivated fruit in the countries of tropical and subtropical climate. Brazil has featured on the world stage, but the accumulation of losses in the production chain of banana is quite large. One way to reduce these losses is to use banana as a source of starch and special flours. The starch varies in form and function within and among plant species and even in the same cultivar under different growing conditions. This variability provides starches with diverse properties. In this line, this project aimed to compare the pulp of the green fruit from banana genotypes, as well as physico-chemical properties of starches. Five genotypes of banana were planted in the farm San Manuel/UNESP and cultured in systematic design in split plots (ten plants/plot). The clusters with green fruits were harvested in the first cycle of production and managed in the processing lab of CERAT/UNESP to obtain the starches. Fresh fruits were analyzed for moisture, phosphorus and starch. In order to compare the characteristics of starches of banana genotypes without phosphorus fertilization, these were analyzed for crystallinity, size distribution of granules, scanning electron microscopy, chemical composition, phosphorus content, apparent amylose, resistant starch, pasting and thermal properties, swelling power and solubility. The analysis reveals that the fruits of 'Prata-Anã' had a higher amount of dry matter (41.95 %). The greatest content of starch in fruit was observed in 'Maçã'. The content of phosphorus in fruit does not differed statistically. The granules of banana starches were large (36.58 to 47.24 microns), oval, had crystallinity standard type B and index of crystallinity with statistically similar values (31.94 % to 34.06 %). The results also showed that the native starches extracted from green bananas had phosphorus contents ranging from 0,003 % ('Grand Naine') ...